(untitled) (Raparin Journal of Humanities (RJH), 2024)
The aim of this study is to determine the effect strategic impact of cognitive activators and advanced organizations on the development of divergent thinking thinking about history among social science students The research subject is the students of the Department of Social Sciences. The research option is the second year students of the Department of Social Sciences. The researcher chose this stage for two reasons The researcher used an experimental design for thirty balanced groups, the first experimental group being the subject of Kurdish history in the Middle Ages The second experimental group received the subjects according to the strategy of advanced organizations. The third group received the subjects according to the normal strategy Out of (57) students, each group has (19) students and researchers A construct for long-term thinking with the number of items was (30) items of questions at (6) levels of questions The following conclusions: • Cognitive activation strategies are a successful way to teach history. • According to the strategy of advanced organizations, it is successful and effective for the subject of history among the students of the department of social sciences and the development of Divergent thinking.